1986
DOI: 10.1103/physrevb.34.4766
|View full text |Cite
|
Sign up to set email alerts
|

Multicritical points in an Ising random-field model

Abstract: The phase diagram of the mean-field Ising model in a random field obeying a symmetric threepeak distribution is determined. This distribution is relevant to diluted antiferromagnets in a uniform magnetic field. The phase diagram includes a fourth-order point, tricritical points, ordered critical points, critical end points, and a double critical end point. An ordered phase persists for arbitrarily large random fields at low temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 18 publications
5
63
0
2
Order By: Relevance
“…The criteria for determining the order of the low temperature phase transition and its dependence on the form of the field distribution have been discussed throughout the years [37,[67][68][69][70][71][72][73]. In fact, different results have been proposed for different field distributions, like the existence of a tricritical point at the strong disorder regime of the system, present only in the bimodal distribution [37,69].…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for determining the order of the low temperature phase transition and its dependence on the form of the field distribution have been discussed throughout the years [37,[67][68][69][70][71][72][73]. In fact, different results have been proposed for different field distributions, like the existence of a tricritical point at the strong disorder regime of the system, present only in the bimodal distribution [37,69].…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the Sherrington-Kirkpatrick spin glass in the presence of random fields {h i }, following a trimodal (three-peak) probability distribution, which corresponds to a bimodal plus a probability p 0 for field dilution, i.e., P ( distribution [15] is washed way by the presence of the delta at the origin, whenever p 0 becomes greater than a certain value [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Aharony [15] argued that whenever an analytic symmetric distribution for the fields presents a minimum at zero field, one should expect a tricritical point and a first-order transition for sufficiently low temperatures. Further studies of the RFIM at the mean-field level have considered a trimodal (three-peak) distribution [17,18] (1 − p 0 ). Such a distribution, which may be interpreted as a bimodal added to a dilution in the fields with probability p 0 [17], is expected to mimic better real systems than its bimodal counterpart.…”
mentioning
confidence: 99%
“…This in turn indicated that the two models should be in the same universality class. Further studies along these lines, using meanfield and renormalization-group approaches, provided contradicting evidence for the critical aspects of the p = 1/3 model and also proposed several approximations of its phase diagram for a range of values of p [40][41][42]. Only very recently accurate numerical data at zero temperature have been presented at d = 3, indicating that the original suggestion of Mattis is most probably correct [43].…”
Section: Introductionmentioning
confidence: 99%